Genetic diversity of Xanthomonas campestris pv. campestris isolated from Brassica crops using RAPD and Rep-PCR - SINGH, DINESH; RATHAUR, PRIYANKA SINGH; SINGH, ASHWARIYA; RAGHUWANSHI, RICHA (The Indian Journal of Agricultural Sciences, 2015)
Xanthomonas campestris pv. campestris (Xcc) is causal agent of black rot disease in crucifers. Genetic diversity, 28 isolates of Xcc collected from cole crops (cauliflower, cabbage, broccoli and knol khol), turnip, brown and yellow mustard crops from northern region of India was performed by using rep-PCR fingerprinting (BOX, REP and ERIC) and random amplified polymorphic DNA (RAPD). Five DNA type groups were formed by using rep-PCR fingerprinting. In RAPD study, six primers showed monomorphic bands and remaining six primers (OPB-10, OPB- 15, UBC-245, D-11, UBC-220 and OPA-11) exhibited polymorphic amplified product in all isolates of Xcc. Xcc- C281 and Xcc-C261 and Xcc-C268 were formed separate group as DNA types, 1, 2, 3, 4, 5 and 6 respectively. Genetic variability was found among the isolates of Xcc based on their hosts. They were categorized into eight groups at DNA typing at 50% similarity coefficient and formed 8 DNA type groups at 50% similarity coefficient. Eighteen isolates of Xcc were grouped under DNA type 7, whereas in DNA type 8 (4 isolates).